States of Incarceration: an architectural perspective on immigrant detention in Texas. (2nd January 2017) - Lopez, Sarah
ABSTRACT: Buildings and landscapes are crystallizations of dominant societal beliefs and practices. Architecture also shapes peoples' experiences of places and institutions, and provides a unique source of evidence of historical change. This article describes how students from the School of Architecture and the Humanities at the University of Texas at Austin researched the spaces of migrant detention in Texas, which is a critical part of America's larger story of mass incarceration. Students mapped the physical locations, architectural forms, and building histories of Texas' detention centers, and worked with migrants who had been detained to create visual stories of their migration journeys and experiences in detention. These methods support the argument that the spaces of immigrant detention – the material forms, geographic locations, institutional structures, and nested experiences – are critical to understanding a disjuncture between detention policy and detention practice. The US government asserts that immigrant detention is civil in nature, yet detention centers owned by private prison corporations and located in unpopulated rural localities with limited public access replicate US prisons, and are experienced by migrants as punitive environments. These methods also contribute to a more robust and expansive public "spatial imagination" regarding the relationship between immigrant detention and the environment, which is necessary to envisioning alternative systems of (and to) immigrant detention.